PENGARUH SELF-HELP GROUPS TERHADAP PENURUNAN DEPRESI PADA MANTAN PEMAKAI NARKOBA DI LEMBAGA PEMASYARAKATAN PEREMPUAN - Ilma Widiya Sari Sari; Mateus Sakundarno Adi; Megah Andriany (Universitas Nahdlatul Ulama Surabaya, 2018)
Depression among prisoners is also found in many female former drug users. Treatment to prevent the negative effects of depression should be immediately provided for the former drug users. Self-help groups as an alternative strategy to improve the support system to create an adaptive coping that can reduce depression level. The purpose of this study was to analyze the effect of self-help groups on depression level in former drug users. The research design used was pre-experiment with one group pre-test and post-test design. Sampling technique using purposive sampling, where only the former drug users who used as sample 19 respondents. Depression level were assessed using Beck Depression Inventory (BDI) II. The result of paired t-test showed that the mean of depression rate has decreased statistically significant, where p value is less than alpha (0,022<0,05). It can be concluded that there is effect of self-help groups on depression level in former drug users